Effectiveness of Low Cost FOSSEE Laptops in a CS101 Course (International Conference on Computers in Education, 2016)
This paper presents a case study of 278 first year students enrolled in a CS101 course of the department of Computer Science at the Indian Institute of Technology Bombay. The sufficiency of a low cost (Rs.7,500 or $110) laptop for this course is assessed. From the feedback questionnaires, the students' perception on the likability of this device is assessed. It is found that the students like this device. Users of this device used it as much others who had access to more expensive computers, and also performed as well as others in the course. This device is useful for several other applications also, and hence is a candidate for mass deployment in developing countries, such as India.